Noxious weed monitoring at the U.S. Air Force Academy: year 7 results - Lavender, Amy, author; Rondeau, Renée Jane, author; Colorado Natural Heritage Program, publisher (Colorado State University. Libraries, 2012)
This report includes a summary of the results of the past seven years of population monitoring of targeted noxious weeds at the US Air Force Academy ("the Academy"), emphasizing changes that were observed between 2010 and 2011.
Prepared for: U.S. Air Force Academy, Dept. of Natural Resources.
Keywords: noxious weeds; Colorado; weed control; vegetation surveys